Análise econômica da recuperação judicial: um estudo sobre a eficiência do processo de recuperação - Martinho, Daniel Möller (Universidade do Vale do Rio dos Sinos, 2018)
The present work aims to analyze the process of judicial reorganization of companies and evaluation of its efficiency as an instrument to overcome the economic and financial crisis. To this end, the study, which uses the method of Law and Economics, is based on the qualitative and quantitative analysis of 181 judicial reorgatization proceedings filed between 09/01/2013 and 06/30/2016 in the 1st and 2nd Bankruptcy Court of the Central Civil Forum of the Region of São Paulo. In addition, as an empirical basis, it seeks to identify all the measurable aspects of the processes studied and to analyze them in the light of the economic theories applicable to Law and Economics, in order to measure the efficiency of the judicial reorganization process in Brazil and the factors that contribute to its higher or lower efficiency. The results suggest that informational asymmetry is the factor that has the greatest impact on the efficiency of the process of judicial reorganization.
Keywords: Recuperação judicial; Eficiência; Assembleia geral de credores; Análise econômica do direito; Judicial reorganization; Efficiency; Creditors’ and equity security holders’ committees; Law and economics; ACCNPQ::Ciências Sociais Aplicadas::Direito